Exposure to xylene and ethylbenzene. III. Effects on central nervous functions. - Gamberale, Francesco; Annwall, Görell; Hultengren, May (Scandinavian Journal of Work, Environment & Health, 1978)
The effect of exposure to the solvent xylene on performance of tests of numerical ability, reaction time (simple and choice), short-term memory, and critical flicker fusion was studied in two separate laboratory series. In the first series fifteen healthy male subjects were studied individually on three separate occasions with exposure to 435 and 1,300 mg/m3 xylene in inspired air and under control conditions. In a second series eight of the subjects were exposed to 1,300 mg/m3 xylene in inspired air. This exposure period began with 30 min of work on a bicycle ergometer (100 W) and continued during the behavioral tests. The procedure was the same under control conditions. Each exposure period lasted 70 min. At certain times during exposure, samples of the subjects alveolar air were collected. Exposure to xylene did not cause any noticeable change in performance during the first laboratory series, when the subjects` total uptake of xylene was estimated to be on an average 180 and 540 mg, respectively. In the second series the physical work induced an increase in the total uptake up to an average of 1,200 mg. In this series clear evidence of performance decrement was observed in three of the performance tests.
Keywords: behavioral effect; central nervous function; central nervous system; ethylbenzene; exposure; human exposure; industrial solvent; psychological function; xylene